EFFECT OF YTTRIUM IRON GARNET (YIG) FILM THICKNESS ON MAGNETIC PROPERTIES AND MICROWAVE RESPONSE: COMPREHENSIVE REVIEW - Anthoni Stanpo, Vito
Telecommunication development encourages higher frequency utilization such as 5G and also microwave components miniaturization such as a smaller circulator. There has been much research about YIG soft ferrite to pursue these goals. The usage of YIG is desirable due to its customizable magnetic properties to match its specifications for circulator application. The advancement of telecommunication requires the miniaturization of telecommunication components such as circulators. As a result, there is an emerging interest in using YIG films for microwave applications. Despite its advantages, the usage of YIG film brings some demerit to its magnetic properties and microwave response, which needs further studies. This review investigates literature that discusses the synthesis of YIG film to observe its magnetic properties and its performance in circulator applications. The constraints in this study are frequency of interest between 4 – 10 GHz, YIG without any dopant, and disk-shaped ferrite in the circulator. Collecting data from various literature was done to give information regarding the phase conversion in YIG films, YIG film magnetic properties, and YIG film thickness effect on its magnetic properties and microwave response. Various data will be presented in tables and graphs, and the correlation of each variable will be analyzed. This study shows that YIG film thickness affects its magnetic properties, linewidth, and microwave response for high-frequency circulators. Apart from thickness, both surface roughness and synthesis methods also contribute to determining YIG film magnetic properties. The pure YIG phase can be obtained through the formation of YIP phases and then followed by YIG phase at the appropriate temperature and holding time. Upper limit for YIG film thickness is inversely correlated with frequency of interest. On the other hand, YIG film thickness larger than 100 ???????? is the lower limit. At lower thickness, surface effect will become dominant in determining YIG film magnetic properties, linewidth, which will be resulting in high insertion loss microwave response.